2017
DOI: 10.1186/s12887-017-0833-9
|View full text |Cite
|
Sign up to set email alerts
|

Congenital malformations and medical conditions associated with orofacial clefts in children in Burkina Faso

Abstract: BackgroundOrofacial clefts are usually isolated cases but can be associated with other congenital malformations that are either recognised or unrecognised syndromes. The reported prevalence and pattern of such associated malformations, however, vary among studies. Objectives: To assess the frequencies and aetiologies of congenital malformations and associated medical conditions in children with orofacial clefts in Burkina Faso (Western Africa).MethodsA retrospective descriptive study was carried out at the El … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
(74 reference statements)
2
15
0
Order By: Relevance
“…20 A considerable number of associated comorbidities were found in the studied patients, especially anemia, followed by respiratory problems and cardiovascular diseases. These findings are in line with those observed by Dvivedi and Dvivedi, 21 who identified anemia in most of the 4,657 CL/P cases studied in India, 21 and by Nagalo et al, 22 who found anemia as the most frequent comorbidity in 185 children with CL/P, followed by respiratory infections in Western Africa. The same results were obtained by Kulkarni et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…20 A considerable number of associated comorbidities were found in the studied patients, especially anemia, followed by respiratory problems and cardiovascular diseases. These findings are in line with those observed by Dvivedi and Dvivedi, 21 who identified anemia in most of the 4,657 CL/P cases studied in India, 21 and by Nagalo et al, 22 who found anemia as the most frequent comorbidity in 185 children with CL/P, followed by respiratory infections in Western Africa. The same results were obtained by Kulkarni et al (2013).…”
Section: Discussionsupporting
confidence: 91%
“…Children with low birth-weight and with cleft lip and palate associated with other congenital malformations are more likely to be born with weight below normal 20,21 . Patients with orofacial clefts have additional risks of malnutrition and anaemia due to feeding problems 6 . Regarding mother's age, the majority were young, under the age of 29, a condition similar to that described in literature 13,22 .…”
Section: Discussionmentioning
confidence: 99%
“…A study of children with orofacial clefts in Burkina Faso found that up to 40% had anemia. 18 Moreover, there is evidence that in low-income settings, severe anemia may be associated with postoperative complications. 19 Fortunately, there were no in-hospital deaths in the present cohort, although Zhang and colleagues have noted that the clinical complications associated with cleft repair may precipitate grave and even fatal consequences in some cases.…”
Section: Discussionmentioning
confidence: 99%